Ultrasensitive detection of proteins and sugars at single-cell level. Issue 1 (2nd January 2016) - Watabe, Satoshi; Morikawa, Mika; Kaneda, Mugiho; Nakaishi, Kazunari; Nakatsuma, Akira; Ninomiya, Masaki; Yoshimura, Teruki; Miura, Toshiaki; Ito, Etsuro
ABSTRACT: Each cell produces its own responses even if it appears identical to other cells. To analyze these individual cell characteristics, we need to measure trace amounts of molecules in a single cell. Nucleic acids in a single cell can be easily amplified by polymerase chain reaction, but single-cell measurement of proteins and sugars will require de novo techniques. In the present study, we outline the techniques we have developed toward this end. For proteins, our ultrasensitive enzyme-linked immunosorbent assay (ELISA) coupled with thionicotinamide-adenine dinucleotide cycling can detect proteins at subattomoles per assay. For sugars, fluorescence correlation spectroscopy coupled with glucose oxidase-catalyzed reaction allows us to measure glucose at tens of nM. Our methods thus offer versatile techniques for single-cell-level analyses, and they are hoped to strongly promote single-cell biology as well as to develop noninvasive tests in clinical medicine.